Monitoring construction of soil nailing using microsoft access / Maheran Zainuddin - Zainuddin, Maheran (Faculty of Civil Engineering, 2006)
This study focused on the development of a computer program for monitoring of soil nailing in construction field by using a Microsoft Access database system. The monitoring of soil nailing in the construction field will be systematic by using the Microsoft Access database system. In this project, the material, machinery, manpower and money aspect (4M) will be monitored by using this system. The data from the site in this project will be collected and key- in in the Microsoft Access database system that was being developed. In this project, a database system will be monitoring their usage, quantity, and cost, finished work on that day or other days. From this system we can reduce the entire item and also know the schedule of the work every time we want. We will use a wizard to rapidly create the structure for a sophisticated contact management database, complete with tables, queries, forms and reports. After exploring this database and entering a few records to get an idea of what a wizard can provide in the way of a starting point, we will discard this database and start working on monitoring the soil nailing. This system is a systematic method in collecting data and minimizes the material, man power, machinery and also the money in soil nailing in construction engineering.